Urbanizing the Regional Sector to Strengthen Economy and Business to Recover from Recession: Proceedings of the 5th International Research Conference on Economics and Business (IRCEB 2021), Malang, Indonesia, 10–11 November 2021 - Aulia Herdiani; Agus Hermawan; Setya Ayu Rahmawati; Mohd. Rizal Palil; Reza Havies (CRC Press, 2023)
This pandemic does not only affect health aspects but also economic aspects. The world today faces a recession resulting from the covid-19 pandemic. Indonesia's economy continues to lead to a recovery, although not very significant. The current government continues to make various recovery efforts. One of the flagship programs includes encouraging and strengthening support for social protection and increasing the purchasing power of households as well as various business sectors, including small and medium-sized micro enterprises (MSMEs). This condition urges the world to create new breakthroughs to rise from this adversity. Academicians and practitioners need to work together to find the necessary solutions and developments. Surely, it will contribute to solve the problems in society by interdisciplinary cooperation. This collaboration will create innovations in science and technology especially business and economic field. This book includes in-depth discussions between academicians and practitioners, especially on how to strengthen the regional sectors to be the strong pillars of the country's economy. Interestingly, various methods are used to observe the problems, to explore the solutions, and to develop the innovation. This book will be of interest to students, scholars, and practitioners of social empowerment, governance, and other related stakeholders. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license. Funded by State University of Malang.
Keywords: 330; governance; regional economy; social empowerment